Comparative study between product- and service-based operations using time-driven activity-based costing - Mohd Yazid, Abu; S N A M, Zaini (IOP Publishing, 2021)
Product-based companies are consumer suppliers that can meet the customer order and consumption. Service-based operation is a company offering an intangible and non including sales and satisfactions type of product. This work aims to summarize the strength of time-driven activity-based costing (TDABC) implementation in product- and service based operation using selected criteria. There are 8 criteria to be discussed are cost allocation, determination of drivers, transparency, cost consideration for implementation, transparency, overestimation of cost, oversimplification of activities and capacity forecast and planning. For product-based operation, this work is conducted at the plantation located in Prosper Palm Oil Mill Sdn. Bhd., Muadzam Shah, Pahang. The estate is divided into three main activity centers which are nursery, replanting and ramp. For service-based operation, data are taken from academic library in Universiti Malaysia Pahang, Pekan, Pahang. However in this work, only two activity centers are been used which are acquisition and cataloging. In this work, the application of TDABC in product- and service-based operations does not present any substantial differences in unused capacity. However, the activities in a product-based company depend on one another in terms of process dependence. While activities are independent in service-based operations.